Overview of property price and its influencing factors in Malaysia - Haron, Razali; Ibrahim, Khairunisah (2016)
Property price hike creates headaches to several parties most significantly home buyers, policy makers and the government itself. Not confined to only the developing economies, the developed nations also face similar problem. As a result, extensive investigations and discussions have been carried out to identify significant determining factors of property price hike in the attempt to understand the property market price behaviour better. By using quarterly data of house price index (HPI), macroeconomic data and financial market data, this study is to examine the behaviour of property price in Malaysia and its influencing factors from the years 2000 to 2015. A bound testing approach to cointegration and error correction models, developed within an Autoregressive Distributed Lag (ARDL) framework ARDL is employed to determine whether property price in Malaysia is explained by fundamental factors or other unexplained factors such as speculation. The findings from this study show that, based on the different segments of house prices, none of the variables is consistently having significant relationship with house price. Inconclusive results are recorded throughout the variables, indicating that those common factors are not able to explain, comprehensively the behaviour of property price in Malaysia during the period understudy. This is interpreted as the existence of speculative activities in local property market thus influences the behaviour of the prices. This study contributes to the literature by identifying the existence of speculation activities in local property market and has policy implication. Policy makers should work in hand with other responsible parties to investigate further the influence of speculation on property price aiming at addressing the price hike phenomenon.